Genetic Profiling of Non‐Small Cell Lung Cancer at Development of Resistance to First‐ or Second‐Generation EGFR‐TKIs by CAPP‐Seq Analysis of Circulating Tumor DNA. (25th April 2019) - Otsubo, Kohei; Sakai, Kazuko; Takeshita, Masafumi; Harada, Daijiro; Azuma, Koichi; Ota, Keiichi; Akamatsu, Hiroaki; Goto, Koichi; Horiike, Atsushi; Kurata, Takayasu; Nakagaki, Noriaki; Nosaki, Kaname; et al.
Abstract: : Patients with non‐small cell lung cancer (NSCLC) treated with epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) eventually acquire resistance to these drugs. The identification of various resistance mechanisms for determination of subsequent treatment for these patients will require a method for simultaneous detection of multiple genetic alterations with high sensitivity. We performed cancer personalized profiling by deep sequencing (CAPP‐Seq) with circulating tumor DNA obtained from patients with NSCLC who acquired resistance to first‐ or second‐generation EGFR‐TKIs. Plasma samples from 27 patients were analyzed, and 24 samples underwent CAPP‐Seq successfully. Original activating EGFR mutations were detected in 23 patients, with the remaining patient showing MET amplification. With regard to known mechanisms of EGFR‐TKI resistance, the T790M mutation of EGFR was detected in 17 of the 24 patients, MET amplification in 9 patients (6 of whom also harbored T790M), ERBB2 amplification in 2 patients (1 of whom also harbored T790M), and EGFR amplification in 4 patients (all of whom harbored T790M). Our results thus show that CAPP‐Seq is applicable to clinical samples for the identification of multiple somatic mutations in circulating tumor DNA obtained from patients with NSCLC at the time of disease progression during treatment with first‐ or second‐generation EGFR‐TKIs. Patients positive for the T790M mutation of EGFR were also found to constitute a molecularly heterogeneous population. Key Points: CAPP‐Seq is applicable to clinical samples for the identification of multiple somatic mutations. The T790M mutation of EGFR is associated with amplification of MET, ERBB2, or EGFR in NSCLC patients resistant to EGFR‐TKIs. T790M‐positive patients are molecularly heterogeneous, and genetic alterations coexisting with T790M may differ between patients treated with first‐generation or second‐generation EGFR‐TKIs. Abstract : This study performed cancer personalized profiling by deep sequencing (CAPP‐Seq) with circulating tumor DNA, a ctDNA‐based form of targeted next‐generation sequencing, to identify somatic mutations in patients with non‐small cell lung cancer (NSCLC) positive for activating mutations of the epidermal growth factor receptor (EGFR) gene at the time of disease progression during treatment with first‐generation (gefitinib or erlotinib) or second‐generation (afatinib) EGFR tyrosine kinase inhibitors.